Association between plasma Vitamin B5 levels and all‐cause mortality: A nested case‐control study. Issue 7 (14th June 2022) - Hong, Yuan; Zhou, Ziyi; Zhang, Nan; He, Qiangqiang; Guo, Zhangyou; Liu, Lishun; Song, Yun; Chen, Ping; Wei, Yaping; Xu, Qiuyue; Li, Ya; Wang, Binyan; et al.
Abstract: We aimed to evaluate the prospective association of vitamin B5 with all‐cause mortality and explore its potential modifiers in Chinese adults with hypertension. A nested, case‐control study was conducted in the China Stroke Primary Prevention Trial, including 505 deaths of all causes and 505 matched controls. The median follow‐up duration was 4.5 years. The primary outcome measure in this investigation was all‐cause mortality, which encompassed deaths for any reason. The mean plasma vitamin B5 concentration for cases (43.7 ng/mL) was higher than that in controls (40.9 ng/mL) ( p = .001). When vitamin B5 was further assessed as quintiles, compared with the reference group (Q1: < 33.0 ng/mL), the risk of all‐cause mortality increased by 29% (OR = 1.29, 95% CI: 0.83‐2.01) in Q2, 22% (OR = 1.22, 95% CI: 0.77‐1.94) in Q3, 62% (OR = 1.62, 95% CI: 1.00‐2.62) in Q4, and 77% (OR = 1.77, 95% CI: 1.06‐2.95) in Q5. The trend test was significant ( p = .022). When Q4‐Q5 were combined, a significant 41% increment (OR = 1.41, 95% CI: 1.03‐1.95) in all‐cause death risk was found compared with Q1‐Q3. The adverse effects were more pronounced in those with normal folate levels ( p ‐interaction = .019) and older people ( p ‐interaction = .037). This study suggests that higher baseline levels of plasma vitamin B5 are a risk factor for all‐cause mortality among Chinese patients with hypertension, especially among older adults and those with adequate folate levels. The findings, if confirmed, may inform novel clinical and nutritional guidelines and interventions to optimize vitamin B5 levels.